Groundwater Contaminant and Resource Management - Salik Javaid, Muhammad (IntechOpen, 2016)
Water inside the earth, the groundwater and the invisible resource is the most important source of survival of mankind on this globe. Part of the hydrological cycle between entry (percolation and recharge) and exit (natural or forced extraction and discharge), the groundwater fascinates all: engineers, hydrogeologists, agriculturists, environmentalists, scientists, academia, resource managers and domestic and industrial users. This book is the outcome of efforts of those eminent authors who despite their fascination were able to write upon some important facet of groundwater flow and the transport of pollutants with it. The dimensions covered range from simple descriptive narratives; to expose of analytical methods; to complex mathematical treatment; to numerical simulations and computer modeling. All areas have been touched upon for the sake of general readers, students, professional engineers and scientists.